Typology of “Displased criticism” in scientific pedagogical dialogues as a methodological phenomenon - A. V. Korzhuev; N. V. Golovina; N. A. Kontarov; Yu. B. Ikrennikova (Образование и наука)
Introduction.  Modern dialogue in the sciences of education plays an extremely important role as a tool for making scientifically based decisions, as a means of evaluating the productivity of innovations proposed by various authors. However, the practice of modern scientific discussions in pedagogy fixes a lot of problems. The organisation of dialogues, which are correct from the point of view of logic and content, and participants carefully listen to their partners and adequately perceive and analyse the proposed solutions to the author’s intentions, is a rather serious problem. Nevertheless, the analysis of the literature on the research topic, the analysis of “live” dialogues in the field of education shows that the authors and participants often violate the rules of logically and meaningfully correct discourse. The author’s criticism of predecessors presented in many dialogues suffers from many shortcomings, which can be briefly summarised as “displaced criticism” – this means shifting the focus of criticism from real errors and inconsistencies to minor flaws and carelessness. Therefore, the authors of the present research considered it necessary to carry out methodological “intervention” in the problem of correct dialogue in pedagogy.   These circumstances, supported by the findings of European education researchers, determine the relevance of the chosen topic.   Aim. The current research aims to: a) construct and substantiate the typology of fragments of “biased criticism”, their thesis display; b) display “displaced criticism” as a methodological negative and a stimulus for the research reflective activity of the pedagogical scientific community.   Methodology and research methods. The research methods involved the analysis of records of scientific dialogues and scientific texts for the content and logical correctness of the justifications for pedagogical conclusions and their criticism; construction and substantiation of the typology of the components of the field under study; reflection of the result and identification of promising vectors for the development of the designated topic.   Results. The results of the study are a typology of fragments of “displaced criticism”, including: a) uncritical isolation of fragments of the reviewed text (or oral dialogue) – regardless of how they were presented by the criticised author himself/herself; b) attribution to the author of incorrect conclusions that he/she did not put forward; c) criticism of illusory consequences from the statements of the author of the text or the participant in the dialogue; d) criticism that clearly demonstrates the substantive ignorance of the participant in the dialogue; e) criticism with inextricably linked elements, which are artificially isolated and there is a distorted form of connection between the elements; f) criticism that deliberately focuses the reader’s attention on minor errors in the text or fragment of the dialogue and misses significant errors. In addition to the justified typology, “displaced criticism” is presented in the format of a methodological negative (1), and the process of its identification as an incentive for scrupulous research activities in pedagogy (2).   Scientific novelty. The scientific novelty consists in proposing and substantiating the typology of methodologically incorrect fragments of “displaced criticism” in pedagogical oral and textual dialogues, as well as in positioning the phenomenon under study as a methodological negative and an incentive for research reflective activity in scientific pedagogy.   Practical significance. The practical significance of the results lies in finding such forms of displaying criticism towards the participants in the dialogues, towards the texts of predecessors, which must be avoided in every possible way, participating in scientific discussions, criticising the results obtained by the authors of articles and books.